ALTERNATIF MODEL PEMBANGUNAN EKONOMI INDONESIA MENGHADAPI ERA GLOBALISASI - Ahmad Buchari1 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
The Indonesian economic development which emphasized on economic growth hasresulted in prolonged multi-crisis. The crisis has caused personal imbalance withinoverall development stakeholders in addition to structural and hierarchal ones. Defying these phenomena, two, preferably-combined, strategies should be taken into action: first, revitalizing or empowering micro, small and medium enterprises as community-based economic development; and second, re-actualizing social development in conjunction with economic development. Through these strategies, it is expected that redistribution with high economic growth can sustainably be achieved.